1985
DOI: 10.1083/jcb.100.2.508
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of human cell lines with 5-azacytidine may result in profound alterations in clonogenicity and growth rate.

Abstract: Liquid medium cultures of three human cell lines (B-lymphoma, myeloma, and squamous lung carcinoma) with population-doubling times (PDT) and cloning efficiencies (CE) in the range of 32-43 h and 0.01-5.6%, respectively, were exposed to 5-azacytidine (5-azaC) for 3 d. The doses used (1-3/zM) were found to be nontoxic as measured by cell growth in liquid and semisolid agar medium and to be nonmutagenic as measured by the rate of generation of ouabain-and 6-thioguanine-resistant cell variants. After 5-azaC trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1985
1985
1990
1990

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 32 publications
(13 reference statements)
1
4
0
Order By: Relevance
“…We have obtained increased metastasis in two tumour lines, a murine [48] and a human [107] melanoma, following brief exposure to low concentrations (3-5/zM) of aza-C. Similar results have been obtained in other murine tumours [108][109][110], while the in vitro clonogenicity and growth rates of human tumour lines, presumed indicators of malignant capacity, have been increased by comparable protocols [117]. While initial treatments with aza-C brought about significant decreases (about 50%) in the percentage of methylated cytosine residues, this extensive hypomethylation was not maintained in lung turnout nodule-derived cell lines [107].…”
Section: Alterations In Gene Expressionsupporting
confidence: 68%
“…We have obtained increased metastasis in two tumour lines, a murine [48] and a human [107] melanoma, following brief exposure to low concentrations (3-5/zM) of aza-C. Similar results have been obtained in other murine tumours [108][109][110], while the in vitro clonogenicity and growth rates of human tumour lines, presumed indicators of malignant capacity, have been increased by comparable protocols [117]. While initial treatments with aza-C brought about significant decreases (about 50%) in the percentage of methylated cytosine residues, this extensive hypomethylation was not maintained in lung turnout nodule-derived cell lines [107].…”
Section: Alterations In Gene Expressionsupporting
confidence: 68%
“…During studies on the cellular phenotypes of 3 human malignant cell lines, it has been recently observed that 5-azaC treatment may induce profound changes in the proliferative activity as expressed by significantly shorter PDT and higher CE (Olsson et al, 1985). The PDT and CE values obtained by 5-azaC treatment were comparable to the fastest growing rodent cell lines, and since the 5-azaC doses were non-mutagenic and non-toxic, the experiments indicate that the human genome does contain a gene repertoire that upon appropriate activation can result in cell populations with PDT and CE values comparable to rodent cell systems.…”
Section: Discussionmentioning
confidence: 99%
“…The schedule for treatment with 5-azaC (Sigma, St. Louis, MO) has been described in detail elsewhere (Olsson et al, 1985). Briefly, cells were exposed for 3 days to 3 pM 5-azaC dissolved in RPMUFCS, then washed and resuspended in RPMUFCS, and aliquots of cells were cloned in semi-solid agar medium for 16 days.…”
Section: Treatment With 5-azac Tpa and Ramentioning
confidence: 99%
“…Intratumoral phen otyp ic diversity is well established for a numb er of phenot yp ic featu res and experiment ally confirmed in many experimen tal as well as huma n tumo r type s (14, 2B). Antigen ic heterogene ity in human lung cancer cell lines was recentl y de scribed and the impact on analysis with Mabs discussed (31)(32)(33). Of significant impo rtance, and only analyzed to a very limited extent , is the intratumoral phen otypic diversity in the stem cell populati on that is the crucial cellular sou rce for maintenance and expansion o f the cell population.…”
Section: Methods Of Product Ion For Antibod Ies Against Tumor• Associmentioning
confidence: 99%